Drug’s analithycal investigation - Cristina, T. Romeo,; Tita, D.,; Eugenia Dumitrescu,; Tita, B. (Medicamentul Veterinar, 2009)
Chemical analysis is the main method of drugs’ investigation. It is currently used in all scientific fields that have a greater or lesser connection with the chemistry. In a simple way we can say that the chemical analysis consists into the characterization of the analyzed system. Characterization means the obtaining and processing of all linked information that allowing the substances or components identifying of the system analysis – so called analytical information.Analytical information is obtained through the complex investigation (analysis) of the studied substance or of the analyzed system (the analytical system). This investigation is done through the monitoring and measurement of certain properties (P) depending on the concentration (C) or volume (V). Instrumental methods can be used to determine other substances characteristics as: determination of some analytical constants, structure determination, the reaction mechanisms elucidation, etc. Practice has shown that the best results are obtained for an analytical method by coupling the chemical techniques with the instrumental ones. In this report are presented the main features, and analytical methods used in the drugs testing.